Development of a three-dimensional arm strength prediction model - Hughes, R. E.; Westreich, A.; Rock, M. G.; An, K. (1997)
The model predicted the ratio of pull up to push down strength when the humerus was in a neutral posture. Statistically significant differences between measured values and model predictions were found in all other test conditions. The largest difference was found in the push/pull forces with the arm abducted 45 degrees.